Sero-Prevalence of Hepatitis B and Hepatitis C in District Sialkot: Prevalence of Hepatitis B and C in Sialkot - Qureshi, Asma Waheed; Jabeen, Farah; Mehmood, Madiha (Pakistan Journal of Health Sciences, 2024)
Hepatitis B and hepatitis C are peak overwhelming infectious conditions belonging to liver inflammation. According to the World Health Organization’s hepatitis report, 96% of the 1.3 million hepatitis virus-related fatalities annually, of which 720,000 happened at the cirrhosis stage, were the result of chronic infections with the hepatitis B and hepatitis C viruses. Objectives: To assess the sero-prevalence of Hepatitis B and Hepatitis C in District Sialkot. Methods: A total of 1,737 blood samples were randomly collected from participants who visited the hospital for hepatitis screening from March 2018 to August 2018. All the samples were screened via Immune-chromatographic strip test. Statistical analysis was performed on data using IBM SPSS Statistics (Version 27). Results: A total of 15.5% samples tested positive, out of which 12.43% samples were hepatitis C viruses and 2.82% were hepatitis B viruses positive respectively. Overall prevalence was higher in male (16.60%) than female 14.19%. Sero-prevalence was high between the age group of 61-80 years. Likewise, among married persons (17.16%) as compared to unmarried (8.01%). Conclusions: It was concluded that a significant association of prevalence of hepatitis with both age and marital status (p<0.001) was observed, while no significant effect was on gender.